PERIPHYTON COMMUNITY STRUCTURE OF ENHALUS ACOROIDES IN BALURAN NATIONAL PARK, SITUBONDO - Arifianti, Dwi Nurjanatin; Dewi, Citra Satrya Utama; Isdianto, Andik (Journal of Environmental Engineering and Sustainable Technology, 2023)
Periphyton is an attached biota that lives on a substrate. Seagrass meadows and periphyton associate to form an ecological system. Seagrass meadows provide a place of attachment or habitat for periphyton organisms. Periphyton itself is one of the producers of primary productivity in the waters. Baluran National Park is one of the National Parks in which there are land and water habitats, and is a protected area that has natural and native ecosystems. Data collected to support this research included temperature, salinity, dissolved oxygen, pH, nutrients (nitrate and phosphate), seagrass cover data and periphyton data. Physical and chemical water parameters are taken directly on the spot or in-situ. Data collection on seagrass cover and periphyton samples was carried out using a 50 x 50 cm2 quadrant transect. Periphyton community structure analysis includes abundance, diversity index, diversity index and dominance index. Community structure is calculated to determine the community condition of a particular organism, to see its stability and presence in an area.